Locking antlers: A ‘levels of conflict’ analysis of upland deer management in the Scottish Highlands - Callum Leavey-Wilson; Janet Fisher; Sam Staddon (Journal of Rural Studies, 2025)

Water poverty in a ‘Hydro Nation’: Exploring distributional and recognitional water injustice in Scotland - Heather K. Anderson; Heather Price; Sam Staddon (Utilities Policy, 2023)

Making a case for the consideration of trust, justice, and power in conservation relationships - Omar Saif; Aidan Keane; Sam Staddon (Conservation Biology, 2022)
In conservation, trust and justice are increasingly recognized as both intrinsically valuable and critical for successful socioecological outcomes. However, the interdependence between these concepts has not been explored. The conservation trust literature provides examples of efforts to build trust between conservationists and local actors; yet, these interventions are often conceived to incentivize local cooperation within dominant paradigms. We argue that when trust building is promoted as a technical fix that does not plan in advance to address power asymmetries in conservation practice, inequities may inadvertently be re‐embedded. Therefore, we conceptualized a framework that joins trust, justice, and power so that critical analyses of conservation partnerships can be more effectively undertaken. We drew on environmental justice theory to better calibrate the trust literature for the historical‐political settings of conservation, especially in the Global South. Justice and trust share strong theoretical links where perceptions of justice shape a willingness to trust, and, equally, trust is a precondition for justice to be perceived. Different forms of trust connect to varied domains of justice and power in different ways, which mediates the outcomes of interventions. We applied our framework to case studies to explore how these interdependences play out in practice. Failure of agencies to attend to issues of maldistribution, misrecognition of cultural values and knowledge, and exclusion from participation strongly compromised trust. Moreover, the ways in which nature‐dependent communities and marginalized conservation workers are trusted, or the conditions under which they give trust, can lead to partnerships being perceived as just or unjust. Focusing on trust and justice can help identify power dynamics so they can be addressed more readily and create space for alternative understandings of partnerships.